Monkeypox Diagnosis by Cutaneous and Mucosal Findings - de Sousa, Diogo (2022)
A monkeypox outbreak has been reported in several countries since early May 2022. Human monkeypox (MPX) diagnosis is based on a clinical suspicion supported by typical skin and mucosal lesions, confirmed with molecular testing. We present the results of all MPX confirmed patients presenting to our department until July 15 of 2022, describing the characteristics of the lesions at diagnosis. In total, 47 patients were included, all men and 44.7% (n = 21) were HIV-positive. Skin lesions were noted in all patients. The most commonly affected area was the genital region (63.8%), followed by the anorectal region (46.8%). Extra anogenital mucosal (oral or conjunctival mucosa) involvement was reported in three patients. Typical skin findings included erythematous papules, whitish, umbilicated papules, some with a necrotic center and an elevated whitish border. Most patients had lesions in multiple phases presenting simultaneously. Correct identification of MPX skin and mucosal lesions is crucial to avoid late diagnosis and prevent further spreading, ensuring less worldwide morbidity.